(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The internal control is the tool through which it is possible to verify and ensure the implementation of tasks in accordance with the established plans and programs and to evaluate the level of performance that is implemented within the different companies. A guarantee from the supplier with the absence of a specialized technical committee that follows up the stages of implementing the contract and disbursing all amounts of financial dues to the supplier before completing the implementation of the contract and overlooking the non-implementation of some clauses of the contract by the committee in charge of examination and receipt, and finally the lack of commitment to the correct accounting classification of the disbursement operations. The aim of the study is to highlight the importance of auditing procedureAnd identifying the nature and forms of accounting creativity and indicating its importance in auditing contracts and demonstrating the efficiency of the systems, laws and legislation issued by the Bureau of Financial Supervision, while determining the nature of the impact of the relationship between the internal audit system and accounting creativity in the research sample, based on the analysis of the responses of the individuals selected for the study. The study was based on a basic hypothesis that there is a statistical relationship between activating the role of internal auditing and reducing the methods of accounting creativity. That is, the higher the levels of application of proactive control and previous auditing, the higher the levels of accounting creativity, and vice versa. The study reached commitment to the professional rules issued by the competent authorities, the provision of the appropriate number of trained financial controllers, and the provision of work requirements that help the auditor to exercise his oversight work with ease and high accuracy, in addition to the application of proactive control. And the previous audit and the establishment of training courses for workers in the operating control authorities with activating the role of the internal auditor and providing everything he needs